Back home: What do we teach to a person with heart failure? - Núñez Narváez, Jhoanna Carolina (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2023)
Chronic diseases have the particularity that, since they are prevalent throughout a person's life, it is up to the individual to manage them at home, based on the knowledge they have, the indications given by health professionals, the availability of resources, their own beliefs and the social support they have, thus leaving a large amount of work for health personnel to address. Of the chronic noncommunicable diseases, the most prevalent in the country are those of the circulatory system, including heart failure. * We thank Professor Jhoanna Carolina Núñez Narváez for ceding her chapter of the book Cuidado CON-VER-GENTE: "Artesanías en Investigación" compiled by Galvis López, Milena Alexandra (Coord.) Tunja: Editorial UPTC, 2019.